Spatio-temporal Evolution and Influencing Factors Analysis of Coordinated Development between Urbanization and Water Resources in Yunnan Province - HAN Lihong; PAN Yujun; GAO Qingyan; LIAO Xuewen (Renmin Zhujiang)
Taking Yunnan Province as the study area, this research constructs an evaluation index system for urbanization and water resources. By employing methods such as the coupling coordination degree model, Dagum's Gini coefficient, and the obstacle degree model, the temporal and spatial evolution and influencing factors of the coupling coordination degree between urbanization and water resources from 2010 to 2021 are analyzed. The study shows that: ① From 2010 to 2021, the urbanization index of Yunnan Province shows a steady growth trend, while the water resources index is a "W"-shaped fluctuation trajectory, with the overall level of system coupling and coordination developing upward. ② In 2010, 2015, and 2021, the spatial development differences in the coupling coordination degree of cities and states are significant, and the overall level is improved; the overall difference of the coupling coordination degree fluctuates with a small decline, and the development difference is the largest in central Yunnan, and the smallest in western Yunnan; the main source of geographical development imbalance is the inter-area difference. ③ The utilization rate of water resource development, the proportion of urban employed population, the per capita green space area of parks, the proportion of secondary and tertiary industries, the amount of urban sewage generation, per capita water resources, and precipitation are the main factors restricting the coordinated development of urbanization and water resources.